The Effect Of The Low Oil Prices On The Algerian Economy An analytical study from 1986 to 2016 - Adjadj, Fatima Zohra; Kalil, Zeyneb (Finance and Business Economies Review, 2019)
The objective of this study is to know the effect of the low oil prices on the Algerian economy based on standard methods on some economic indicators (oil prices, GDP, real per capita income, unemployment rate) during the period 1980/2016, which proved that all variables are related to oil prices dramatically both at high and low.